Academic Advising Needs among University Students in Kenya - Muola, James M; Migosi, Joash A (International Journal of Asian Social Science, 2012)
It is not easy for the overburdened student counselors in universities to adequately address students’ needs in all areas. Hence, the establishment of academic advising Western countries and recently in some Kenyan institutions. Academic advising should be need-centered for it to be popular with students and to succeed. This study aimed at evaluating students’ academic advising needs so as to enable academic advisors and universities to be able to prioritise when planning for academic mentorship. The study applied the descriptive survey method in which subjects were asked to indicate the areas in which they thought they needed help. A questionnaire was used to collect data. A random sample of 187 (53, 41 and 93 first, second and third year students respectively) participated in the study. Purposive sampling was used to select Laikipia University College of Egerton University which is one of the seven public universities in Kenya. The findings showed that the top ranking academic advising needs were maintaining high grades, handling heavier academic workload, setting career goals, and setting academic goals irrespective of the year of study and gender. It was recommended that students’ needs should be taken into account when planning for academic mentorship activities.